(untitled) (Research, Society and Development, 2020)
Light is essential in the growth and development of plants due to its influence on photosynthesis and photomorphogenesis, so the use of light emitting diodes with emission of photosynthetically active radiation is an alternative to improve seedling growth in an air-conditioned environment. The objective of the work was to evaluate the effect of supplementation of photosynthetically active radiation in the production of seedlings of two varieties of basil. The experimental design used was completely randomized (DIC), in a 2 x 2 factorial scheme, with 4 repetitions, with 20 plants per plot, consisting of supplementation of photosynthetically active radiation (absence and presence) and two varieties of basil (sweet basil and purple basil). The supplementation of photosynthetically active radiation was carried out using a 360W ledgrow lamp from 7:00 am to 11:00 am. The variables analyzed were neck diameter, height-to-diameter ratio, shoot dry mass, root dry mass, total dry mass, plant height and shoot dry mass, Dickson quality index, leaf area, mass ratio aerial part dryness and dry mass of the root system and plant height. In the absence of supplemental RFA, the growth of the varieties of basil was similar, however in the presence of supplementation, the sweet basil variety stood out in greater growth and quality of seedlings.